Negative and positive environmental perspective of COVID-19: air, water, wastewater, forest, and noise quality. Issue 1 (1st January 2021) - Mohapatra, Ranjan K; Das, Pradeep K; Sharun, Khan; Tiwari, Ruchi; Mohapatara, Saumya Ranjan; Mohapatra, Pranab K.; Behera, Ajit; Acharyya, Tamoghna; Kandi, Venkataramana; Zahan, Kudrat-E; Natesan, Senthilkumar; Bilal, Muhammad; et al.
ABSTRACT: The ongoing coronavirus disease 2019 (COVID-19) pandemic driven by severe acute respiratory syndrome coronavirus – 2 (SARS-CoV-2) has become the most critical universal health disaster of this century. Millions of people are staying at home obeying lockdown to halt the spread of this novel virus. The spread of the virus has forced people to use the mask, gloves, hand sanitizer, etc. daily, and healthcare workers to use personal protection equipment following the WHO guidelines, resulting in huge amounts of medical waste. This pandemic has led to a slowdown of economic activities significantly, and consequently, stock markets have nosedived beyond speculation. Although the deadly coronavirus has taken away millions of precious lives and the livelihood of many sections of people worldwide, it has brought several positive changes in the world. Furthermore, it has led to a massive restoration of the environment and improved air and water quality. Pandemic showed the resilient nature of the environment, including air and water, when human activities are paused. In addition, we also discussed how this pandemic affects human lifestyle behavior.